Biological activity of Paecilomyces genus against Toxocara canis eggs - Basualdo Farjat, Juan Ángel (2000)
Saprophytic soil fungi can exert ovicidal and ovistatic effects on helminths with differing degrees of efficiency. The representatives of such fungi from temperate regions, Paecilomyces lilacinus (Thom) Samson and P. marquandii (Masse) Hughes, exhibit recognized ovicidal activity on some nematodes. We evaluated the action in vitro of P. lilacinus and P. marquandii on the zoonotic canine roundworm eggs of Toxocara canis. Eggs exposed and unexposed to fungal samples were observed by both light and scanning electron microscopy on days 4, 7 and 14 post-inoculation. Ovicidal activity of P. lilacinus on T. canis eggs was considered to be high and that of P. marquandii to be intermediate.